Influence of Preoperative Radiation Field on Postoperative Leak Rates in Esophageal Cancer Patients after Trimodality Therapy - Juloori, Aditya (2014)
INTRODUCTION: Postoperative morbidities, such as anastomotic leaks, are common after trimodality therapy (chemoradiation followed by surgery) for esophageal cancer. We investigated for factors associated with an increased incidence of anastomotic leaks. METHODS: Data from 285 esophageal cancer patients treated from 2000–2011 with trimodality therapy was analyzed. Anastomotic location relative to preoperative radiation field was assessed using postoperative computed tomographic imaging. Logistic regression was used to evaluate for factors associated with any or clinically relevant (CR) (≥ grade 2) leaks. RESULTS: Overall anastomotic leak rate was 11% (31/285), and CR leak rate was 6% (17/285). Multivariable analysis identified body mass index (BMI) (OR 1.09, 95%CI 1.00–1.17; OR 1.11, 95%CI 1.01–1.22), three-field surgery (OR 10.01, 95%CI 3.83–26.21; OR 4.83, 95%CI 1.39–16.71), and within radiation field (“in-field”) anastomosis (OR 5.37, 95%CI 2.21–13.04; OR 8.63, 95%CI 2.90–25.65) as independent predictors of both all grade and CR leaks, respectively. While patients with distal esophageal tumors and Ivor-Lewis surgery had the lowest incidence of all grade (6.5%) and CR leaks (4.2%), most of the leaks were associated with the anastomosis constructed within the field of radiation (in-field: 39% and 30% versus out-of-field: 2.6% and 1.0%, respectively, for total and CR leaks, p<0.0001, Fisher’s Exact test). CONCLUSIONS: Esophagogastric anastomosis placed within the preoperative radiation field was a very strong predictor for anastomotic leaks in esophageal cancer patients treated with trimodality therapy, among other factors. Surgical planning should include a critical evaluation of the preoperative radiation fields to ensure proper anastomotic placement after chemoradiation therapy.